# Math

Use the method of substitution to solve the linear equation!
6a=6-b
6a=5-b

1. Look at the two equations. If 6a=6-b, substitute that into the other equation:

(6-b) = 5-b
add b to both sides and you have
6=5

There are no solutions to that "equation".

posted by Steve

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get
2. ### Linear Equations

Can you please help solve this equation using the substitution method? I have tried and keep getting that X and Y = 7/2, but the answer in the book states no solution, inconsistent system. What am I doing wrong? Please help! Solve
3. ### Algebra

Solve this system of linear equations. * Used the substitution method 3x - y = 8 4x - y = -15 ----------------------------------------- WORK y = 3x - 8 4x - (3x - 8 ) = -15 4x - 3x + 8 = -15 x + 8 = -15 x = -7 3x - y = 8 3(-7) - y
4. ### alg 1

use the method of substitution to solve the system of linear equation 2x-y=5, 9x-4y=22
5. ### algebra

use method of substitution to solve the system of linear equation 3x+4y=3/2 y=2x-1
6. ### algebra

Requesting help. (I must reckon, that X is a variable, and y is y-intercept) Q: Try to use the substitution method to solve the the linear system y=3x an y=3x-7. What do you notice? A) What happens when you graph it? B) Explain
7. ### Math

17) solve this linear system using the method of substitution. 2y-x=-10 y= -3/2x-1 20) simplify then solve by substitution 2(x-4)+y=6 3x-2(y-3)=13 just need help with these 2.
8. ### Math

I still don't know how to directly solve this problem. Can someone guide to solve this system of equation by using the substitution method? Thanks! 1. Y=6x-5 Y=-x+9
9. ### Math

Solve the system using any algebraic method. 2x - 2y + z = 3 5y - z = -31 x + 3y + 2z = -21 ______________________ The answer I got for this is ( -26, 6,67) but I know its wrong and I don't know why. Help please >< my work
10. ### Algebra II

How do you solve the linear equations x+y=5 3x-y=3 by use of the Substitution Method? (Please do not confuse with the Elimination Method)

More Similar Questions